Work Factors Associated with Low Back Pain Among Pedicab Drivers: A Cross-Sectional Study - Hasanudin Hasanudin; Saharudin Saharudin; Mustafa Mustafa; Dedi Mahyudin Syam; Fitri Handayani (Poltekkes Kemenkes Palu, 2026)
Background: Pedicab drivers face prolonged sitting, repetitive pedaling, trunk stabilization, and poor seat ergonomics. This study examined associations among posture, working hours, tenure, and LBP at Pasar Inpres in Palu City. Methods: This analytic observational study used a cross-sectional design and was conducted in June 2024 at Pasar Inpres, Manonda Village, Palu Barat District, Palu City. The population comprised all pedicab drivers in the study area, and 51 respondents were recruited via a total sampling approach. LBP was defined as self-reported pain or discomfort in the lower back region at the time of data collection. Sitting posture was assessed using an observation sheet, while working hours, work tenure, and LBP were collected using questionnaires. Data were analyzed using the chi-square test or Fisher’s exact test when appropriate. Prevalence ratios (PRs) and 95% confidence intervals (CIs) were calculated to estimate the magnitude of association. Results: LBP was reported by 38 respondents (74.5%). Non-ergonomic sitting posture was associated with LBP (PR=1.58; 95% CI: 1.08-2.31; p=0.008). Working more than 8 hours/day was also associated with LBP (PR=1.47; 95% CI: 1.04-2.09; p=0.020), as was work tenure of more than 5 years (PR=2.05; 95% CI: 1.21-3.47; p<0.001). Conclusion: LBP was common among pedicab drivers at Pasar Inpres, Palu City. Non-ergonomic sitting posture, working more than 8 hours/day, and work tenure of more than 5 years were significantly associated with LBP. Community-based occupational health programs should prioritize ergonomic sitting education, active rest, stretching, and simple seat support for pedicab drivers.